Audio Visual Media-Based Health Education Increases Knowledge of Menstrual Disorders in Adolescence - Elisa Elisa; Iffah Hanifah; Desak Parwati; Muhamad Jauhar (JENDELA NURSING JOURNAL, 2022)
Background: students' knowledge about menstrual disorders is still inadequate so that it will have an impact on disrupting learning activities, difficulty concentrating, mood changes, anemia, etc. So it is necessary to increase knowledge about menstrual disorders with interesting health education by using audio-visual media.Purpose: to determine the effect of health education with audio-visual media on knowledge of menstrual disorders in adolescents.Methods: this study used a pre-experimental design with a one-group pretest-posttest design. The sampling technique used proportional random sampling technique as many as 41 respondents, the sample selection used the lottery technique. The research instrument used is a questionnaire. Data analysis used the Wilcoxon test.Results: based on the results p-value = 0.000, it can be concluded that there is an effect of health education with audio-visual media on the level of knowledge about menstrual disorders in adolescent girls.Conclusion: it is needed that teenagers can increase their knowledge about menstrual disorders through reading books, electronics, or other printed media so that they can handle menstrual disorders when they occur.